Analisis Kebutuhan Fasilitas Edukasi Pengelolaan Sampah berdasarkan Demografi Kabupaten Sidoarjo - Adinugraha, I Nyoman Anom Bramaprakasa; Masruchin, Febby Rahmatullah (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2024)
Waste is the remaining solid waste formed from natural processes and daily human activities. Waste has the potential to disrupt the environment and public health if not managed or handled properly. In solving this waste problem, it needs to be done comprehensively and integrated from upstream to downstream by the entire community through waste banks. The role of waste banks as one of the waste reduction solutions in Sidoarjo Regency is still not maximized, due to the lack of understanding and ability of the community. Based on this, it is necessary to reduce the volume of waste generation in a sustainable manner through a facility to educate the community as well as a forum for waste management. The purpose of this study is to determine the need for facilities needed to solve waste problems based on demographics in Sidoarjo Regency. This research uses a qualitative descriptive method, the types of data used are qualitative and quantitative data. In collecting data, the author uses primary data through interviews with related government, while secondary data is obtained through media publications such as articles and journals. Based on the results of the analysis, the conclusion is that based on the demographic conditions of Sidoarjo Regency, the facilities needed include: Main Waste Bank, TPS 3R, waste information gallery, recycled art gallery, hall, waste practicum room, auditorium.